Pressure dependence of Poisson's ratio of glassy Baltic amber studied by Brillouin scattering spectroscopy. (17th March 2021) - Tkachev, Sergey N.; Ahart, Muhtar; Novikov, Vladimir N.; Kojima, Seiji
Abstract: Amber is a typical natural glass with very long aging time. Elastic properties of amber at high pressures have been studied using Brillouin scattering and a diamond anvil cell. Both longitudinal and transverse acoustic modes have been observed up to 12 GPa. The pressure dependences of longitudinal, shear, Young's, and bulk moduli, compressibility, and Poisson's ratio were determined. The longitudinal, shear, Young's, bulk moduli show the remarkable increase, and compressibility shows a marked decrease with increasing pressure. However, it is found that the pressure dependence of Poisson's ratio is very small. The mechanism of this small pressure dependence was discussed. The Cauchy type relation between longitudinal and shear moduli was examined. Its coefficients show the deviation from the Cauchy relation owing to the coexistence of different intermolecular interactions in amber.